Water quality purification long-acting slow-release bacterial block, and preparation method and application thereof
Patent Information
- Application Number
- CN202611095844.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]本发明所要解决的技术问题是针对现有水质净化菌块存在的菌种活性保护不足、缓释周期短、结构易开裂及生态安全性差等技术问题,提供一种水质净化长效缓释菌块及其制备方法和应用
本发明的释放菌块包含内核、固态碳源层、塑料壳及卡扣式可拆卸塑料网盖的结构,以及内核由菌种复合颗粒与缓释基材在>100MPa压力下压制成型、渗透系数<10-7cm/s的技术方案,取得了以下有益效果:通过多孔载体刚性骨架在海绵孔隙内部形成应力屏蔽区承担外部应力、结合海藻酸钠干膜弹性缓冲的双重耐压保护机制,实现了>100MPa超高压压制成型与菌种高活性保持的协同,解决了现有技术因低压制片导致孔隙率高、释放周期短的矛盾;超低渗透系数(<10-7cm/s)使水体无法渗入内核内部,内核在水体中呈表面逐层剥蚀状态释放菌种,实现菌块零级释放动力学特征,有效克服了现有技术释放速率不可控、缓释周期短的技术难题;通过由内核-固态碳源层-塑料壳所构成的三层结构配合塑料网盖释放孔的设置,使内核仅通过释放孔与水体单向接触、释放面积大幅削减,同时固态碳源层包覆内核外部提供营养支持,实现释放方向可控与多重功能协同;海藻酸钠干膜由海藻酸钠在不添加任何化学交联剂的条件下经脱水收缩形成,从源头上杜绝了氯离子的引入,彻底消除了传统氯化钙交联工艺中残留氯离子对菌种的慢性毒害、对水生生物的毒性及对金属设备的腐蚀加速效应。上述技术方案共同作用,使菌块在菌种活性保持、释放速率控制、结构完整性和生态安全性方面均显著优于现有技术,实现了长效缓释与高活性的统一。
Smart Images

Figure CN122957972A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water environment management and microbial immobilization technology, specifically relating to a long-lasting slow-release bacterial block for water purification in small water bodies, landscape water bodies and other water bodies with weak self-purification capacity, as well as its preparation method and application. Background Technology
[0002] During the self-purification process of water bodies, organic matter provides nutrients for microbial growth, driving the initial proliferation of functional bacterial communities, followed by a decline due to nutrient depletion, forming a cyclical ebb and flow. When the bacterial community is in a low abundance phase and encounters the input of new pollutants, the number of beneficial bacteria such as nitrifying bacteria, denitrifying bacteria, and organic matter degrading bacteria in the water body is difficult to rapidly proliferate to an effective concentration, making the water body prone to blackening and odor. For small water bodies with poor flow and weak self-purification capacity, as well as artificial landscape water bodies isolated from natural rivers and lakes, the self-purification function is easily degraded or even lost under the continuous impact of external pollution.
[0003] Immobilized microbial technology can significantly improve the stability and activity of microorganisms and reduce the interference of external environmental changes on microorganisms, making it a commonly used technique in the field of water environment management. Based on this principle, various slow-release products have been developed. For example, some methods use porous natural mineral particles as carriers, allowing water-purifying microorganisms to implant in the pores of the particles, utilizing the slow-release function of the porous particles to slowly release live bacteria with the water flow; other methods store bacterial strains in the pores of porous release carriers and attach a biofilm layer to the surface of the carrier to achieve slow release; still other methods produce solid slow-release bacterial balls from heterotrophic nitrifying-aerobic denitrifying strains for use in aquariums and landscape ponds for water purification. In addition, technologies using modified expanded vermiculite as a slow-release substrate and diatomaceous earth and bentonite as microbial inoculant carriers have also been reported. These products achieve the slow release of bacteria to a certain extent.
[0004] While the aforementioned slow-release products achieve a certain degree of slow release of bacteria, several shortcomings remain. First, existing products are not perfect in maintaining bacterial activity. Their immobilization methods mostly rely on physical adsorption or simple encapsulation, lacking a systematic protection design throughout the entire preparation, storage, and operation process. The bacteria are easily inactivated during compression, high-temperature filling, and long-term operation. Water seeps into the bacteria, prematurely activating and continuously consuming them, making it difficult to maintain effective activity long-term. Second, existing products also have limitations in their slow-release structural design. The large surface area of the bacterial blocks exposed to water makes them prone to cracking and damage during carbon source cooling and transportation. Furthermore, the simultaneous consumption of carbon source and bacteria leads to a lack of nutritional support and a sharp drop in purification function after the bacteria are released. Third, some products use calcium chloride-sodium alginate crosslinking systems or synthetic polymers such as polyvinyl alcohol (PVA), posing ecological safety risks such as chloride ion pollution and microplastic residues. The introduction of exogenous bacteria may also impact indigenous microbial communities.
[0005] In other words, how to provide a long-lasting slow-release bacterial block for water purification, its preparation method and application, which can maintain the bacterial activity, long-lasting slow-release performance and product structural integrity of the bacterial block, and improve the ecological and biological safety of the material, is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to address the existing technical problems of insufficient protection of bacterial activity, short slow release period, easy cracking of structure and poor ecological safety of existing water purification bacterial blocks, and to provide a long-lasting slow-release bacterial block for water purification, its preparation method and application.
[0007] To address the aforementioned problems, the first aspect of this invention provides a long-lasting, slow-release bacterial block for water purification. The bacterial block comprises: a core, a solid carbon source layer, a plastic shell, and a snap-on detachable plastic mesh cover. The solid carbon source layer covers the outside of the core, and the plastic shell is disposed outside the solid carbon source layer. The snap-on detachable plastic mesh cover is disposed on the plastic shell. The core comprises: a slow-release substrate, which includes water-soluble inorganic materials, gypsum powder, and / or bentonite; and bacterial composite particles, which comprise a porous carrier and functional bacteria loaded within the pores of the porous carrier. The surface of the porous carrier is covered with a sodium alginate dry film. The bacterial composite particles are formed by mixing the porous carrier with adsorbed functional bacteria and the sodium alginate. The core is formed by pressing the bacterial composite particles and the slow-release substrate under a pressure >100 MPa, with a permeability coefficient <10. -7 cm / s.
[0008] In the first aspect, the porous carrier includes: the porous carrier having a porous structure inside, the functional bacterial strain being loaded within the porous structure, the porous structure forming a stress-shielding chamber for shielding external stress, and the rigid skeleton of the porous carrier bearing external stress to protect the functional bacterial strain inside the pores.
[0009] Specifically, the porous structure of the porous carrier (compressive strength ≥150MPa) forms a stress-shielded chamber. Its function is that when the bacterial block is subjected to 120MPa high pressure for molding in subsequent steps, or under hydrostatic pressure in water, the external force is mainly borne by the continuous rigid skeleton of the porous carrier, while the functional bacteria loaded inside the pores are protected by the skeleton and are not subjected to direct mechanical compression and shearing damage, thereby ensuring a high survival rate of the bacteria under harsh processing conditions.
[0010] In the first aspect, the solid carbon source layer includes beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. The solid carbon source layer is formed by melting and mixing beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. A three-dimensional loofah network is embedded in the solid carbon source layer.
[0011] Specifically, beeswax, as a hydrophobic framework material, ensures the stability of the carbon source layer in water, maintaining its solid state underwater for extended periods. Short cotton fibers, as a reinforcing phase, improve the tensile strength and structural integrity of the carbon source layer, preventing cracking or detachment during transportation, deployment, or water erosion. Skim milk powder, corn cob powder, and starch, as readily available carbon and nutrient sources for microorganisms, can be slowly biodegraded by aquatic microorganisms, continuously releasing small-molecule organic carbon. The embedded three-dimensional loofah network acts as a "steel skeleton," enhancing the overall mechanical strength of the carbon source layer and increasing the contact surface area between the carbon source layer and water through its porous network structure, facilitating uniform dissolution of the carbon source. This formulation combination allows the external carbon source layer to remain stable in a solid state for a long period, achieving slow carbon source release.
[0012] In the first aspect, the plastic shell has no openings in its shell wall to enclose the solid carbon source layer through its non-perforated shell wall.
[0013] Specifically, the closed design of the plastic shell allows the core to exchange substances with the external water only through the top release pore. This precisely defines the single release interface for functional bacteria and carbon sources. By completely sealing the shell, water cannot seep into the core from the sides or bottom. The wetting and erosion process of the core is strictly limited to the local area corresponding to the release pore, thus avoiding the problem of uncontrolled release rates caused by multiple sides of the core being exposed to water simultaneously.
[0014] In the first aspect, the snap-on detachable plastic mesh cover has a release hole.
[0015] Specifically, by precisely controlling the pore size of the release pores, the overflow of porous carrier particles can be limited and the exchange rate between water and the core can be adjusted, thereby achieving precise control over the release flux of microorganisms and the dissolution rate of carbon sources.
[0016] The second aspect of this invention provides a method for preparing a long-lasting, slow-release bacterial block for water purification, comprising the following steps: Step S1: Mixing a porous carrier adsorbed with functional bacteria with sodium alginate, and drying at a temperature below 35°C without adding any chemical cross-linking agent, causing the sodium alginate to shrink and form a dry film coating the surface of the porous carrier, thus obtaining bacterial composite particles; the film coating of sodium alginate is achieved through physical dehydration and shrinkage rather than chemical cross-linking. The absence of chemical cross-linking agents (such as CaCl2) completely avoids the exothermic cross-linking reaction and the thermal damage to the bacteria caused by high osmotic pressure, ensuring a high survival rate of the bacteria from the source; the dry film physically seals the pores of the porous carrier, providing a pre-existing protective barrier for the bacteria before subsequent high-pressure pressing. Step S2: Mixing the bacterial composite particles with a water-soluble inorganic slow-release substrate, adjusting the moisture content to 8%~15%, and pressing under a pressure >100MPa to obtain a permeability coefficient <10. -7 The core has a permeability of cm / s; within this moisture content range, hydrated minerals in water-soluble inorganic slow-release substrates (such as gypsum powder and bentonite) can fully fill the interparticle gaps under high pressure, reducing the core permeability coefficient to 10. -7 The permeability coefficient is below cm / s. The direct effect of this ultra-low permeability coefficient is that after the bacterial block is placed in a water body, water molecules can only permeate and diffuse into the core at an extremely slow rate.
[0017] Step S3: A solid carbon source layer is coated on the outside of the core. The solid carbon source layer exposes the core to water only through a release hole. By setting a solid carbon source layer on the outside of the dense core, the solid carbon source layer not only provides carbon but also further reduces the number of direct material exchange channels between the core and the outside world. The design of unidirectional exposure to water only through the release hole effectively avoids uneven erosion and sudden large-scale release caused by multiple sides of the core contacting water simultaneously.
[0018] The porous carrier is a rigid inorganic porous particle with a compressive strength of not less than 150 MPa, selected from one or more of volcanic rock and ceramsite. The functional bacteria are derived from the indigenous microbial community of the sediment in the area where the water to be treated is located, and the functional microbial community includes at least nitrifying bacteria, denitrifying bacteria, and organic matter degrading bacteria. In the second aspect, the preparation method further includes: pre-cooling the core in an environment of 0℃~10℃. After the core is fully cooled in the environment of 0℃~10℃, its overall heat capacity stores sufficient cold energy. When it is placed in a flowing cold water bath and injected with molten carbon source at 60℃~70℃, the core can quickly absorb the heat at the contact interface, causing the liquid carbon source to begin to solidify rapidly the moment it contacts the core surface.
[0019] In the second aspect, step S3 specifically includes: step S301: placing the pre-cooled core into a matching plastic shell; step S302: placing the plastic shell containing the core into a flowing cold water bath; step S303: pouring molten liquid carbon source into the plastic shell placed in the cold water bath, utilizing the synergistic effect of the core's cold storage effect and the cooling effect of the cold water bath to rapidly cool and solidify the liquid carbon source; wherein, the temperature of the liquid carbon source is 60℃~70℃, and the internal temperature of the core does not exceed 35℃ during the pouring and solidification process of the liquid carbon source.
[0020] In the second aspect, the solid carbon source layer comprises beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. The solid carbon source layer is formed by melting and mixing beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. A three-dimensional loofah mesh is pre-placed in the plastic shell, and a snap-on detachable plastic mesh cover is provided on the plastic shell, with the release hole provided on the plastic mesh cover. The hydrophobic properties of beeswax enable the carbon source layer to maintain its shape well underwater, preventing dissolution and disintegration. The bridging and reinforcing effect of the short cotton fibers prevents cracks in the carbon source layer under cooling contraction or water flow impact. The pre-placed three-dimensional loofah mesh in the plastic shell not only serves as a reinforcing skeleton, improving the tensile and crack resistance of the carbon source layer, but also, due to its three-dimensional porous nature, increases the contact area between the carbon source layer and the external water body, which is beneficial for the uniform and stable release of the carbon source.
[0021] Thirdly, this invention also discloses the application of a long-lasting slow-release bacterial block for water purification. The total amount of bacteria released per unit time is controlled by adjusting the number of bacterial blocks added according to the degree of water pollution, while the slow-release period of a single bacterial block remains constant. A hanging ring is provided on the plastic shell attached to the bacterial block, and the bacterial block is released via a rope connected to the hanging ring. The length of the rope is adjusted according to the water depth, ensuring that the bacterial block sinks above the surface of the bottom sediment. By adjusting the rope length, the bacterial block can be suspended in the water layer above the sediment-water interface, ensuring that the bacterial block is in a relatively oxygen-sufficient water layer, which is beneficial to the synergistic metabolic activities of aerobic nitrifying bacteria and facultative denitrifying bacteria.
[0022] Beneficial effects: The release-type bacterial block of the present invention comprises a core, a solid carbon source layer, a plastic shell, and a snap-on detachable plastic mesh cover. The core is formed by pressing bacterial composite particles and a slow-release substrate under a pressure of >100MPa, and has a permeability coefficient of <10. -7The cm / s technical solution has achieved the following beneficial effects: By forming a stress-shielding zone within the sponge pores through a porous carrier rigid skeleton to bear external stress, combined with the elastic buffering mechanism of sodium alginate dry film, a dual pressure-resistant protection mechanism is achieved, realizing the synergy between >100MPa ultra-high pressure molding and the maintenance of high bacterial activity. This solves the contradiction of high porosity and short release cycle caused by low-pressure sheets in existing technologies; ultra-low permeability coefficient (<10) -7 The system, with a release speed of cm / s, prevents water from penetrating the core. The core releases bacteria through a gradual, surface-to-layer erosion process, achieving zero-order release kinetics and effectively overcoming the technical challenges of uncontrollable release rates and short release cycles in existing technologies. The three-layer structure—core, solid carbon source layer, and plastic shell—combined with the release holes in the plastic mesh cover, ensures the core only contacts the water unidirectionally through these holes, significantly reducing the release area. Simultaneously, the solid carbon source layer provides nutritional support by coating the core, enabling controllable release direction and synergistic multi-functionality. The sodium alginate dry film, formed by dehydration and shrinkage of sodium alginate without any chemical cross-linking agents, eliminates the introduction of chloride ions at the source, completely eliminating the chronic toxicity of residual chloride ions to bacteria, toxicity to aquatic organisms, and accelerated corrosion of metal equipment inherent in traditional calcium chloride cross-linking processes. The combined effect of these technologies results in bacterial blocks that significantly outperform existing technologies in terms of bacterial activity maintenance, release rate control, structural integrity, and ecological safety, achieving a balance between long-term sustained release and high activity. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of this specification or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 This is a schematic diagram of the overall structure of the long-lasting slow-release bacterial block for water purification of the present invention.
[0025] Figure 2 This is a schematic cross-sectional view of the long-lasting slow-release bacterial block for water purification according to the present invention.
[0026] Figure 3 This is a schematic diagram of the microstructure of the bacterial strain composite particles of the present invention.
[0027] Figure 4 This is a schematic diagram comparing the release mechanism of the bacterial block of the present invention (release through layer-by-layer surface erosion) with that of the bacterial block of the prior art (release through internal penetration and diffusion).
[0028] Figure label: 1. Plastic mesh cover; 2. Plastic shell; 3. Solid carbon source layer; 4. Kernel; 5. Three-dimensional network of loofah sponge; 6. Hanging rings; 7. Sodium alginate dry film; 8. Functional strains; 9. Porous carrier. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0030] Example 1 like Figure 1-3 As shown, Embodiment 1 of this application provides a long-lasting slow-release bacterial block for water purification. The bacterial block includes: a core 4, a solid carbon source layer 3, a plastic shell 2, and a snap-on detachable plastic mesh cover. The core 4 is covered with the solid carbon source layer 3, and the solid carbon source layer 3 is surrounded by the plastic shell 2. The plastic shell is fitted with a snap-on detachable plastic mesh cover. The core 4 includes: a slow-release substrate, which comprises water-soluble inorganic materials, gypsum powder, and / or bentonite; and bacterial composite particles, which include a porous carrier 9 and functional bacteria 8 loaded in the pores of the porous carrier 9. The surface of the porous carrier 9 is covered with a sodium alginate dry film 7. The bacterial composite particles are formed by mixing the porous carrier 9 with the functional bacteria 8 adsorbed on it and the sodium alginate.
[0031] Specifically, the mycelium block of the present invention is composed of a core 4, a solid carbon source layer 3, a plastic shell 2, and a snap-on detachable plastic mesh cover. The core 4 is formed by pressing the aforementioned mycelium composite particles and slow-release substrate under a pressure of >100MPa, with a permeability coefficient of <10. -7At a speed of cm / s, the core 4 releases bacteria in the water through a gradual surface erosion process, preventing water from penetrating the core. The core 4 is externally covered by a solid carbon source layer 3, which exposes the core 4 to the water only through release pores. The slow-release period of the solid carbon source layer 3 is longer than the bacterial release period of the core 4. The solid carbon source layer 3 is composed of beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch, all of which are natural plant and animal sources, renewable, and biodegradable. The shell of the substrate 2 has no pores in its shell wall, allowing the solid carbon source layer 3 to be enveloped through its non-porous shell wall; the plastic shell 2 is equipped with a snap-on detachable plastic mesh cover, which has a release hole. After the contents of the bacterial block are exhausted, the plastic shell 2 and the plastic mesh cover can be disassembled, recycled, and reused; the slow-release substrate contains water-soluble inorganic materials, gypsum powder, and / or bentonite. The slow-release substrate of this invention utilizes the slightly soluble properties of gypsum powder and the low permeability of bentonite, combined with high-pressure pressing of >100MPa, to give the bacterial block a low permeability coefficient (<10). - 7 (cm / s) and surface layer-by-layer erosion characteristics - the former prevents water from penetrating into the interior, while the latter ensures that the surface material is slightly dissolved and eroded after contact with water, and the bacteria are released accordingly, achieving zero-order release kinetic characteristics; the bacterial composite particles contain a porous carrier 9 and functional bacteria 8 loaded in the pores of the porous carrier 9. The surface of the porous carrier 9 is covered with a sodium alginate dry film. The bacterial composite particles are made by mixing the porous carrier 9 with adsorbed functional bacteria 8 and sodium alginate. The functional bacteria in the bacterial composite particles are in a metabolic dormant state under the coating of sodium alginate dry film.
[0032] In Embodiment 1, the porous carrier 9 has a porous structure inside, and the functional bacterial strain 8 is loaded inside the porous structure. The porous structure forms a stress-shielding chamber for shielding external stress, and the rigid skeleton of the porous carrier 9 bears the external stress to protect the functional bacterial strain 8 inside the pores.
[0033] In Example 1, the solid carbon source layer 3 includes beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. The solid carbon source layer 3 is formed by melting and mixing beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. A three-dimensional loofah network is embedded in the solid carbon source layer 3. The slow release period of the solid carbon source layer is longer than that of the bacterial strain. After the release is completed, there is a seamless transition to the maintenance buffer period to avoid a cliff-like decline in function.
[0034] In Embodiment 1, the plastic shell 2 has no holes in its shell wall so that the solid carbon source layer can be enclosed by its non-perforated shell wall. By wrapping the outer layer, making the plastic shell wall non-perforated, and only having a mesh cover release hole, the contact area between the core and the water body is reduced by more than 80% (from omnidirectional release on six sides to limited release on one side), and the release rate is reduced to less than 1 / 5.
[0035] In Embodiment 1, the snap-on detachable plastic mesh cover is provided with a release hole. Through the three-layer structure consisting of the core 4, the solid carbon source layer 3, and the plastic shell, combined with the setting of the release hole of the plastic mesh cover, the core 4 only contacts the water body in one direction through the release hole, and the release area is greatly reduced. At the same time, the solid carbon source layer 3 covers the outside of the core to provide nutritional support, so as to achieve controllable release direction and multiple functions in synergy.
[0036] Example 2 Based on a general inventive concept, Embodiment 2 of this application provides a method for preparing a long-lasting slow-release bacterial block for water purification. Specifically, the preparation method includes the following steps: Step S1: Mix the porous carrier with adsorbed functional bacteria with sodium alginate, and dry it at a temperature below 35°C without adding any chemical cross-linking agent, so that the sodium alginate shrinks to form a dry film coating the surface of the porous carrier, thereby obtaining bacterial composite particles. Step S2: Mix the bacterial composite particles with a water-soluble inorganic slow-release substrate, adjust the moisture content to 8%~15%, and press into shape under a pressure of >100MPa to obtain a permeability coefficient <10. -7 kernel speed of cm / s; Step S3: Cover the outside of the core with a solid carbon source layer, the solid carbon source layer exposing the core to water only through a release hole; The porous carrier is a rigid inorganic porous particle with a compressive strength of not less than 150 MPa, selected from one or more of volcanic rock and ceramsite; the functional bacteria are derived from the indigenous microbial community of the bottom sediment of the water body to be treated, and the functional microbial community includes at least nitrifying bacteria, denitrifying bacteria and organic matter degrading bacteria. Prior to step S3, the preparation method further includes: The core was pre-cooled in an environment of 0℃~10℃. Step S3 specifically includes: Step S301: Place the pre-cooled core into the matching plastic shell; Step S302: Place the plastic shell containing the core into a flowing cold water bath; Step S303: Pour the molten liquid carbon source into the plastic shell placed in a cold water bath. Utilize the synergistic effect of the core's cold storage effect and the cooling effect of the cold water bath to rapidly cool and solidify the liquid carbon source. The temperature of the liquid carbon source is 60℃~70℃, and the internal temperature of the core does not exceed 35℃ during the infusion and solidification of the liquid carbon source.
[0037] In Example 2, the solid carbon source layer 3 includes beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. The solid carbon source layer 3 is formed by melting and mixing beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. A three-dimensional loofah mesh is pre-placed in the plastic shell 2, and a snap-on detachable plastic mesh cover is provided on the plastic shell 2. The plastic mesh cover has the release hole. The three-dimensional loofah mesh serves as a structural reinforcement mesh to prevent the solid carbon source layer from cracking. The loofah is a natural plant fiber that can be used as a supplementary carbon source for microbial degradation and utilization.
[0038] In Example 2, the total amount of bacteria released per unit time is controlled by adjusting the number of the released bacterial blocks added according to the degree of water pollution, and the slow release period of a single released bacterial block remains unchanged; a hanging ring is provided on the plastic shell that is matched with the released bacterial block, and the released bacterial block is released by a hanging rope connected to the hanging ring. The length of the hanging rope is adjusted according to the water depth so that the released bacterial block sinks above the bottom sediment surface.
[0039] Example 3 To further illustrate the structural characteristics of the bacterial blocks prepared by the method described in Example 2, the feasibility of the core process parameters, and their beneficial effects on the sustained release of carbon source and functional bacterial community, Example 3 is provided below. Example 3 differs from Example 2 in that it is a more specific implementation based on the same core concept. The differences between Example 3 and Example 2 are as follows: the coating excipients are different: in Example 3, when mixing the porous carrier with sodium alginate, skim milk powder (20g / kg carrier) and gypsum powder (30g / kg carrier) are additionally added as auxiliary film-forming and protective components; Example 3 specifies that the sustained-release substrate is 60 parts by weight of gypsum powder and 40 parts by weight of bentonite, and the mixing weight ratio of the bacterial composite particles to the sustained-release substrate is 1:2, with a specific moisture content of 12%; the liquid carbon source in Example 3 uses 30 parts by weight of beeswax, 5 parts by weight of short cotton fiber, 20 parts by weight of skim milk powder, 30 parts by weight of corn cob powder, and starch... 20 parts by weight of powder were heated to 65°C to melt the powder. In Example 3, a three-dimensional loofah mesh with a pore size of 5-8 mm was pre-placed inside the plastic shell as a supporting skeleton, and the internal dimensions of the plastic shell (5 cm long × 5 cm wide × 5 cm high) and the diameter of the release hole (1.8 mm) were specifically defined. After step S8, Example 3 further included step S9 (sealing the prepared bacterial blocks in aluminum foil bags and storing them in a dry and cool place for later use) and step S10 (releasing the bacterial blocks into simulated water bodies for periodic testing of viable bacteria count and remaining mass) to verify the actual slow-release performance and bacterial release effect of the product.
[0040] Specifically, this embodiment three provides a method for preparing long-lasting slow-release bacterial blocks for water purification, the preparation method including the following steps: Step S1: Take 5 kg of bottom sediment from the area of the water body to be treated, add 1 kg of carbon source (glucose) and 2 L of biological packing material (polyurethane sponge packing material), place it in an aeration tank, and aerate and culture for 7 days at 25-30℃. After biofilm formation on the surface of the biological packing material, allow it to settle to remove the bottom sediment, and take the supernatant, which is the bacterial solution containing enriched functional bacteria. Identification by 16S rRNA high-throughput sequencing revealed that the bacterial solution contains indigenous functional bacteria such as nitrifying bacteria, denitrifying bacteria, and organic matter degrading bacteria. The specific method for enriching and screening indigenous bacteria from bottom sediment is a known technique in this field and can be routinely adjusted according to the actual characteristics of the bottom sediment.
[0041] Step S2: Take volcanic rock particles (particle size 2~3mm, specific surface area >5m²) 2 Add 1 kg of the above bacterial solution (with a compressive strength >150MPa) to the solution and continue culturing at 25~30℃ for 3 days to allow the bacteria to fully penetrate the pores of the volcanic rock.
[0042] Remove the bacteria-laden volcanic rock particles, drain off excess bacterial solution, and add 50g sodium alginate, 20g skim milk powder, and 30g gypsum powder. Mix well. Do not add any chemical cross-linking agents (such as CaCl2, glutaraldehyde, etc.).
[0043] The above mixture was placed in a 30°C constant temperature drying oven for 48 hours to allow sodium alginate to lose water and undergo volume shrinkage, forming a dense glassy dry film that covers the inner walls and pore openings of the volcanic rock, thus obtaining composite microbial particles. Sampling and testing showed a viability rate of approximately 96% of the initial value.
[0044] Step S3: Take 60 parts by weight of gypsum powder (200 mesh) and 40 parts by weight of bentonite (200 mesh), mix them evenly to obtain the slow-release substrate.
[0045] Step S4: Mix the above-mentioned microbial composite particles with the slow-release substrate at a weight ratio of 1:2, add an appropriate amount of deionized water to adjust the moisture content to 12%, and stir thoroughly to ensure that the materials are mixed evenly.
[0046] Step S5: The conditioned mixture is placed into a columnar pressing mold, a pressure of 120 MPa is applied, and the pressure is held for 3 minutes. The core is then demolded to obtain a columnar core (3 cm in length, 3 cm in width, and 4 cm in height). The core permeability coefficient is measured to be 5 × 10⁻⁶. -8 cm / s. The survival rate of bacteria in the core sample was approximately 92%.
[0047] Step S6: Place the pressed kernel in a 40℃ oven to dry for 24 hours to remove residual moisture, and then transfer it to a 4℃ refrigerator to pre-cool for 12 hours.
[0048] Step S7: Take 30 parts by weight of beeswax, 5 parts by weight of short cotton fiber (2-5mm in length), 20 parts by weight of skim milk powder, 30 parts by weight of corn cob powder (100 mesh fineness), and 20 parts by weight of starch. Mix them and heat to 65℃ to melt. Stir to mix evenly to obtain a liquid carbon source.
[0049] Step S8: Place the pre-cooled kernel into the center of the matching plastic shell (internal dimensions: length 5cm, width 5cm, height 5cm; external dimensions: length 5.2cm, width 5.2cm, height 5.2cm); a three-dimensional loofah mesh (pore size 5~8mm) is pre-placed inside the plastic shell. Place the entire plastic shell in a flowing cold water bath, with only the top filling port protruding above the water surface.
[0050] Liquid carbon source at 65℃ was injected into the plastic shell through the filling port, filling the inner cavity of the shell, and then the plastic mesh cover (the release hole diameter is 1.8mm, smaller than the diameter of the porous particles) was closed. Utilizing the synergistic effect of the core's heat storage effect and the forced cooling effect of the cold water bath, the liquid carbon source rapidly solidified upon contact with the core. Temperature monitoring showed that the internal temperature of the core never exceeded 35℃.
[0051] Step S9: Seal the prepared mycelium blocks in aluminum foil bags and store them in a dry, cool place for later use.
[0052] Step S10: The bacterial blocks prepared in Example 1 are placed in a simulated water body (25°C static water body, bacterial blocks suspended above sediment) using a suspension rope, and samples are taken periodically to detect the number of live bacteria and the remaining mass of the bacterial blocks in the water.
[0053] Release curves show that the bacterial blocks exhibit zero-order release kinetics (constant release rate per unit time) from 0 to 6 months. At 6 months, the cumulative released bacterial count reaches over 85% of the total bacterial load. After 6 months, the release rate gradually decreases, but solid carbon sources continue to be released, providing nutritional support for the released bacteria attached to the volcanic rock particles, maintaining the functional bacterial population in the water. Significant bacterial replenishment is still detectable until the 8th month. Viability testing shows that the viability of each batch of released bacteria is >90%.
[0054] Water purification effect test: In simulated polluted water (initial COD about 80 mg / L, ammonia nitrogen about 15 mg / L), after adding the bacterial blocks of this invention, the COD removal rate reached 85% and the ammonia nitrogen removal rate reached 85% on the 7th day; the COD removal rate reached 90% and the ammonia nitrogen removal rate reached 90% on the 30th day; after continuous operation for 6 months, the COD removal rate was stably maintained at 90%~95% and the ammonia nitrogen removal rate was stably maintained at 85%~90%.
[0055] A comparison between Example 3 and Example 2 leads to the following conclusions: The bacterial blocks prepared in Example 3 exhibit the following characteristics: Low-temperature drying at 30℃ allows sodium alginate to self-shrink and form a protective film, maintaining a viable bacterial rate of 96%; high-pressure molding at 120MPa achieves a permeability coefficient of 5×10⁻⁶. -8 The dense core, with a density of cm / s, achieves a 92% survival rate for bacterial strains. Utilizing a combination of core pre-cooling and cold water bath, the core temperature is kept below 35°C during the injection of molten carbon source at 65°C, preventing thermal damage. In terms of effectiveness, the outer solid carbon source undergoes slow biodegradation, continuously supplying small-molecule carbon sources and preventing one-time depletion. The ultra-low permeability coefficient of the core, combined with the gradual swelling of the membrane, allows for the slow, stepwise release of functional bacteria. Simulated water body experiments confirm that the bacterial blocks can effectively replenish carbon sources and continuously release nitrifying, denitrifying, and organic matter-degrading bacteria, achieving sustained enhancement of water self-purification and denitrification.
[0056] Furthermore, to illustrate the effects of the porous carrier, moisture content, pressing pressure, and solid carbon source ratio on the core permeability coefficient in Example 3, Example 4 is provided below. The difference between Example 4 and Example 3 is that the porous carrier is ceramsite (particle size 2-4 mm, specific surface area > 4 m²). 2 / g, compressive strength >130MPa); moisture content adjusted to 10%; pressing pressure 150MPa; carbon source ratio: beeswax 25 parts by weight, short cotton fiber 3 parts by weight, skim milk powder 25 parts by weight, corn cob powder 25 parts by weight, starch 25 parts by weight.
[0057] Example 4: This embodiment four provides a method for preparing a long-lasting slow-release bacterial block for water purification, the preparation method including the following steps: Step S1: Take 5 kg of bottom sediment from the area of the water body to be treated, add 1 kg of carbon source (glucose) and 2 L of biological packing material (polyurethane sponge packing material), place it in an aeration tank, and aerate and culture for 7 days at 25-30℃. After biofilm formation on the surface of the biological packing material, allow it to settle to remove the bottom sediment, and take the supernatant, which is the bacterial solution containing enriched functional bacteria. Identification by 16S rRNA high-throughput sequencing revealed that the bacterial solution contains indigenous functional bacteria such as nitrifying bacteria, denitrifying bacteria, and organic matter degrading bacteria. The specific method for enriching and screening indigenous bacteria from bottom sediment is a known technique in this field and can be routinely adjusted according to the actual characteristics of the bottom sediment.
[0058] Step S2: Take ceramsite (particle size 2~4mm, specific surface area >4m²) 2 / g, compressive strength >130MPa) 1kg, put into the above bacterial solution, and continue to culture at 25~30℃ for 3 days to allow the bacterial strain to fully enter the pores of the volcanic rock.
[0059] Remove the bacteria-laden volcanic rock particles, drain off excess bacterial solution, and add 50g sodium alginate, 20g skim milk powder, and 30g gypsum powder. Mix well. Do not add any chemical cross-linking agents (such as CaCl2, glutaraldehyde, etc.).
[0060] The above mixture was placed in a 30°C constant temperature drying oven for 48 hours to allow sodium alginate to lose water and undergo volume shrinkage, forming a dense glassy dry film that covers the inner walls and pore openings of the volcanic rock, thus obtaining composite microbial particles. Sampling and testing showed a viability rate of approximately 96% of the initial value.
[0061] Step S3: Take 60 parts by weight of gypsum powder (200 mesh) and 40 parts by weight of bentonite (200 mesh), mix them evenly to obtain the slow-release substrate.
[0062] Step S4: Mix the above-mentioned microbial composite particles with the slow-release substrate at a weight ratio of 1:2, add an appropriate amount of deionized water to adjust the moisture content to 10%, and stir thoroughly to make the materials evenly mixed.
[0063] Step S5: The conditioned mixture is placed into a columnar pressing mold, a pressure of 150 MPa is applied, and the pressure is held for 3 minutes. The core is then demolded to obtain a columnar core (3 cm in length, 3 cm in width, and 4 cm in height). The core permeability coefficient is measured to be 3 × 10⁻⁶. -8 cm / s. The survival rate of bacteria in the core sample was approximately 91%.
[0064] Step S6: Place the pressed kernel in a 40℃ oven to dry for 24 hours to remove residual moisture, and then transfer it to a 4℃ refrigerator to pre-cool for 12 hours.
[0065] Step S7: Take 25 parts by weight of beeswax, 3 parts by weight of short cotton fiber, 25 parts by weight of skim milk powder, 25 parts by weight of corn cob powder, and 25 parts by weight of starch. Mix them and heat to 65°C to melt. Stir to mix evenly to obtain a liquid carbon source.
[0066] Step S8: Place the pre-cooled kernel into the center of the matching plastic shell (internal dimensions: length 5cm, width 5cm, height 5cm; external dimensions: length 5.2cm, width 5.2cm, height 5.2cm); a three-dimensional loofah mesh (pore size 5~8mm) is pre-placed inside the plastic shell. Place the entire plastic shell in a flowing cold water bath, with only the top filling port protruding above the water surface.
[0067] Liquid carbon source at 65℃ was injected into the plastic shell through the filling port, filling the inner cavity of the shell, and then the plastic mesh cover (the release hole diameter is 1.8mm, smaller than the diameter of the porous particles) was closed. Utilizing the synergistic effect of the core's heat storage effect and the forced cooling effect of the cold water bath, the liquid carbon source rapidly solidified upon contact with the core. Temperature monitoring showed that the internal temperature of the core never exceeded 35℃.
[0068] Step S9: Seal the prepared mycelium blocks in aluminum foil bags and store them in a dry, cool place for later use.
[0069] Step S10: The bacterial blocks prepared in Example 2 are placed in a simulated water body (25°C static water body, bacterial blocks suspended above sediment) using a suspension rope, and samples are taken periodically to detect the number of live bacteria and the remaining mass of the bacterial blocks in the water.
[0070] Release curves show that the bacterial blocks exhibit zero-order release kinetics (constant release rate per unit time) from 0 to 6 months. At 6 months, the cumulative released bacterial count reaches over 85% of the total bacterial load. After 6 months, the release rate gradually decreases, but solid carbon sources continue to be released, providing nutritional support for the released bacteria attached to the volcanic rock particles, maintaining the functional bacterial population in the water. Significant bacterial replenishment is still detectable until the 8th month. Viability testing shows that the viability of each batch of released bacteria is >90%.
[0071] Water purification effect test: In simulated polluted water (initial COD about 80 mg / L, ammonia nitrogen about 15 mg / L), after adding the bacterial blocks of this invention, the COD removal rate reached 85% and the ammonia nitrogen removal rate reached 85% on the 7th day; the COD removal rate reached 90% and the ammonia nitrogen removal rate reached 90% on the 30th day; after continuous operation for 6 months, the COD removal rate was stably maintained at 90%~95% and the ammonia nitrogen removal rate was stably maintained at 85%~90%.
[0072] By comparing Example 4 and Example 3, the following conclusions can be drawn: Under the same conditions, using ceramsite (particle size 2-4mm, specific surface area >4m²) as the porous carrier yields the following results: 2 / g, compressive strength >130MPa); moisture content adjusted to 10%; pressing pressure 150MPa; solid carbon source ratio: beeswax 25 parts by weight, short cotton fiber 3 parts by weight, skim milk powder 25 parts by weight, corn cob powder 25 parts by weight, starch 25 parts by weight, core permeability coefficient 5×10 -8 cm / s decreased to 3×10 -8 The microbial survival rate after compression is approximately 91% (cm / s). The release performance is basically the same as in Example 3, with a sustained-release period of more than 6 months.
[0073] To illustrate the effect of the absence of crosslinking agent on the performance of the bacterial block in Example 3, Comparative Example 1 is provided below. The difference between Comparative Example 1 and Example 3 is that in the preparation step of the bacterial composite particles, sodium alginate is added along with CaCl2 solution (final concentration 2%) to crosslink and solidify the sodium alginate.
[0074] Comparative Example 1: The basic steps are the same as in Example 3, except that in the preparation step of the bacterial composite particles, sodium alginate is added at the same time as CaCl2 solution (final concentration 2%) to crosslink and solidify the sodium alginate.
[0075] The comparison between Comparative Example 1 and Example 3 leads to the following conclusions: After the composite particles were prepared, the viable bacterial rate decreased to approximately 65% (due to the osmotic pressure impact of CaCl2 and thermal damage from the chemical reaction). After being pressed at 120 MPa, the cross-linked sodium alginate gel brittlely fractured, failing to effectively protect the bacterial strain. The viable bacterial rate after pressing was only about 50%. Simultaneously, the brittle fractured sodium alginate gel affected the permeability of the bacterial block, with the core permeability coefficient approximately 10. -5 The release test showed that the bacterial blocks were completely released within 2 weeks at a speed of cm / s, and the released bacterial strains had low activity. Water body testing showed that chloride ions were continuously dissolved during the release process, and the chloride ion concentration in the water increased compared to the background value. These experimental results prove that the absence of chemical cross-linking agents in this application is a necessary prerequisite for achieving high viability, ultra-low permeability coefficient, long-lasting zero-stage slow release, and avoiding secondary pollution.
[0076] To illustrate the effect of high-pressure pressing on the performance of the mycelium blocks in Example 3, Comparative Example 2 is provided below. The difference between Comparative Example 2 and Example 3 is that the pressing pressure is 50 MPa (conventional low-pressure tablet pressure).
[0077] Comparative Example 2: The basic steps are the same as in Example 3, except that the pressing pressure is 50 MPa (the pressure of a conventional low-pressure tablet).
[0078] The comparison between Comparative Example 2 and Example 3 leads to the following conclusion: the core penetration coefficient is approximately 10. -5 At a pressure of cm / s, water can penetrate into the microbial block. Release tests showed that the microbial block released all its contents within one month, with the release curve exhibiting a "fast at first, slow later" decay pattern, which does not conform to zero-order release kinetics. These experimental results demonstrate that high-pressure molding at greater than 100 MPa is a necessary process condition for obtaining an ultra-low permeability core and ensuring a stable and controllable slow-release cycle.
[0079] To illustrate the effect of the unidirectional release structure in Example 3 on the performance of the bacterial block, Comparative Example 3 is provided below. The difference between Comparative Example 3 and Example 3 is that both the plastic shell and the plastic mesh cover have release holes, and the core is exposed to water on multiple sides.
[0080] Comparative Example 3: The basic steps are the same as in Example 3, except that: both the plastic shell and the plastic mesh cover have release holes, and the core is exposed to water on multiple sides.
[0081] The comparison between Comparative Example 3 and Example 3 leads to the following conclusions: the contact area between the core and water is approximately 6.7 times that of Example 1 (100% vs 15%), resulting in a significantly faster release rate and a shorter sustained-release period of approximately 2 months. These experimental results validate the necessity of the "one-way confined release" structural design of this invention, where the plastic shell wall is pore-free and only the top mesh cover has a release hole. By limiting the core's sole exposed interface to a single release hole, the material exchange rate can be precisely controlled, achieving long-term, stable, zero-level sustained-release.
[0082] Therefore, it can be seen that the present invention relies on the synergistic effect of three core technologies: "non-crosslinking self-shrinking encapsulation - high-pressure compaction molding - unidirectional confined release," none of which can be omitted. Comparative Example 1 shows that adding CaCl2 crosslinking agent causes the viable bacteria rate to plummet to 65%, and high-pressure pressing leads to brittleness and a permeability coefficient as low as 10. -5 The release rate was cm / s and the release cycle was only 2 weeks, while introducing chloride ion contamination, proving that not adding chemical cross-linking agents is a prerequisite for ensuring bacterial activity and membrane flexibility; Comparative Example 2 shows that 50 MPa low-pressure suppression reduced the core permeability coefficient to only 10. -5 The release rate was measured at cm / s, exhibiting a "fast initially, slow later" decay pattern with a release period of less than one month, demonstrating that high pressure (>100 MPa) is a necessary condition for obtaining ultra-low permeability and zero-order slow-release kinetics. Comparative Example 3 showed that bidirectional pores increased the contact area between the core and water by 6.7 times, shortening the release period to approximately two months, proving that unidirectional release pores are a key structural design for precisely controlling the release interface and extending the release duration. Only through the synergy of these three factors can a 92% viable bacterial count and a permeability of 5 × 10⁻⁶ be achieved after compression. -8 With a release rate of cm / s and a zero-level slow release duration of several months, while avoiding secondary chemical pollution, it provides a highly efficient and long-lasting slow-release bacterial agent for in-situ water remediation.
[0083] Finally, it should be noted that the above embodiments are merely specific implementations of the present invention, used to illustrate the technical solutions of the present invention, and not to limit it. The scope of protection of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments within the scope of the technology disclosed in the present invention, or make equivalent substitutions for some of the technical features; and these modifications, changes, or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. All should be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
[0084] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.
Claims
1. A long-lasting, slow-release bacterial block for water purification, characterized in that, The microbial block comprises: a core, a solid carbon source layer, a plastic shell, and a snap-on detachable plastic mesh cover. The core is covered by the solid carbon source layer, and the plastic shell is disposed on the outside of the solid carbon source layer. The snap-on detachable plastic mesh cover is disposed on the plastic shell. The kernel includes: The sustained-release substrate comprises water-soluble inorganic materials, gypsum powder and / or bentonite; The microbial composite particles comprise a porous carrier and functional microorganisms loaded within the pores of the porous carrier. The surface of the porous carrier is covered with a sodium alginate dry film. The microbial composite particles are formed by mixing the porous carrier with the adsorbed functional microorganisms with the sodium alginate. The core is formed by pressing the microbial composite particles and the slow-release substrate under a pressure of >100MPa, with a permeability coefficient of <10. -7 cm / s.
2. The water purification long-acting slow-release bacterial block according to claim 1, characterized in that, The porous carrier includes: The porous carrier has a porous structure inside, and the functional bacteria are loaded in the porous structure. The porous structure forms a stress-shielding chamber for shielding external stress. The rigid skeleton of the porous carrier bears the external stress to protect the functional bacteria inside the pores.
3. The water purification long-acting slow-release bacterial block according to claim 1, characterized in that, The solid carbon source layer includes beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. The solid carbon source layer is formed by melting and mixing beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. A three-dimensional loofah network is embedded in the solid carbon source layer.
4. The water purification long-acting slow-release bacterial block according to claim 1, characterized in that, The plastic shell has no holes in its shell wall so as to enclose the solid carbon source layer through its non-perforated shell wall.
5. The long-lasting slow-release bacterial block for water purification according to claim 1, characterized in that, The snap-on detachable plastic mesh cover has a release hole.
6. A method for preparing a long-lasting, slow-release bacterial block for water purification, used to prepare the long-lasting, slow-release bacterial block for water purification as described in any one of claims 1-5, characterized in that, The preparation method includes the following steps: Step S1: Mix the porous carrier with adsorbed functional bacteria with sodium alginate, and dry it at a temperature below 35°C without adding any chemical cross-linking agent, so that the sodium alginate shrinks to form a dry film coating the surface of the porous carrier, thereby obtaining bacterial composite particles. Step S2: Mix the bacterial composite particles with a water-soluble inorganic slow-release substrate, adjust the moisture content to 8%~15%, and press into shape under a pressure of >100MPa to obtain a permeability coefficient <10. -7 kernel speed of cm / s; Step S3: Cover the outside of the core with a solid carbon source layer, the solid carbon source layer exposing the core to water only through a release hole; The porous carrier is a rigid inorganic porous particle with a compressive strength of not less than 150 MPa, selected from one or more of volcanic rock and ceramsite; the functional bacteria are derived from the indigenous microbial community of the bottom sediment of the water body to be treated, and the functional bacteria include at least nitrifying bacteria, denitrifying bacteria and organic matter degrading bacteria.
7. The method for preparing long-lasting slow-release bacterial blocks for water purification as described in claim 6, characterized in that, Prior to step S3, the preparation method further includes: The core was pre-cooled in an environment of 0℃~10℃.
8. The method for preparing long-lasting slow-release bacterial blocks for water purification as described in claim 7, characterized in that, Step S3 specifically includes: Step S301: Place the pre-cooled core into the matching plastic shell; Step S302: Place the plastic shell containing the core into a flowing cold water bath; Step S303: Pour the molten liquid carbon source into the plastic shell placed in a cold water bath. Utilize the synergistic effect of the core's cold storage effect and the cooling effect of the cold water bath to rapidly cool and solidify the liquid carbon source. The temperature of the liquid carbon source is 60℃~70℃, and the internal temperature of the core does not exceed 35℃ during the infusion and solidification of the liquid carbon source.
9. The method for preparing long-lasting slow-release bacterial blocks for water purification as described in claim 8, characterized in that: The solid carbon source layer includes beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. The solid carbon source layer is formed by melting and mixing beeswax, short cotton fibers, and one or more of skim milk powder, corn cob powder, and starch. The plastic shell contains a three-dimensional loofah mesh, and the plastic shell is provided with a snap-on detachable plastic mesh cover, which has a release hole.
10. The application of a long-lasting slow-release bacterial block for water purification as described in any one of claims 1-5, characterized in that, The total amount of bacteria released per unit time is controlled by adjusting the number of bacterial blocks added according to the degree of water pollution, while the slow release period of a single bacterial block remains unchanged. The plastic shell that is attached to the release block is equipped with a lifting ring. The release block is released by a rope connected to the lifting ring. The length of the rope is adjusted according to the water depth so that the release block sinks above the surface of the bottom sediment.
